The Role of a Writer: Reflections of a Novelist - Yadav, Prabhu Ray (Tribhuvan University Journal, 2017)
Chinua Achebe is an iconic name in Africa as well as world literature. He is a writer committed to the social uplift of marginalized and downtrodden people. He believes that serious writer should have a sense of responsibility to enhance the quality of humanity by way of exposing all manmade suppression and oppression in society. Achebe is a crusader against colonialism that enslaved the African countries and their people. He is opposed to the injustice and atrocities perpetrated by colonial rulers, and he wants to awaken the African people to rise up against the onslaught of colonialism in future. The present work serves as an inspiring guide to the African people and writers to pursue the spirit of struggle to gain self dignity and recognition. He writes with a missionary zeal and exhorts the writers to use their art as a weapon to assert their confidence and past glory. For him, art is a means to bring about change in society. His works have served as a teacher for his readers. So, Achebe has become a novelist cum teacher, especially for African people, and in general for his readers all over the world.